Towards Improved Local Level Planning for Rural Development Case Study of Kundrakudi, Tamil Nadu - Planning Commission (Planning Commission, 1985)
Kundrakudi's experience shows the nature and dimension of the development administration problem in the rural areas. In the first place, the choice of the peasants below the poverty line to be helped is not an easy task. It requires careful survey of the village and considerable verification of facts. When this is done by a body of villagers themselves with no secrecy behind it, then no mistakes are made and no undue favours are shown to anyone in particular.
Multilevel Planning Division Planning Commission Government of India
Multilevel Planning Division Planning Commission Government of India